A crystalline glaze powder, a crystalline glaze, crystalline ceramic tiles, and a method for preparing them.

By using a method for preparing crystalline glaze powder, combined with raw materials such as quartz stone and acidic yttrium aluminum composite, a one-time firing of crystalline ceramic tiles was achieved, solving the problems of surface strength and cost, improving wear resistance and smoothness, and reducing production costs.

CN118239683BActive Publication Date: 2026-01-30QINGYUAN GANI CERAMICS CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410331625.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2026-01-30
Estimated Expiration
2044-03-22

AI Technical Summary

Technical Problem

Existing imitation marble ceramic tiles have shortcomings in terms of surface strength and production cost. Multiple firing processes result in significant material loss, affecting tile deformation and flatness.

Method used

The preparation method of crystalline glaze powder includes a combination of quartz, feldspar, potassium feldspar, sodium feldspar, limestone, dolomite and crystalline composite dry granule slurry. The surface strength is improved by firing once, and acidic yttrium aluminum composite and ultrafine dry particles are added to form crystalline composite dry granule slurry. Crystalline glaze is prepared by ball milling and calcination processes.

Benefits of technology

It achieves high wear resistance and static friction coefficient of crystalline ceramic tiles, high surface flatness, reduces production costs, and prevents inkjet patterns from losing color during high-temperature firing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118239683B_ABST
    Figure CN118239683B_ABST
Patent Text Reader

Abstract

This invention relates to the field of ceramic tile technology, specifically to a crystalline glaze powder, a crystalline glaze, crystalline ceramic tiles, and a preparation method. This application provides a crystalline glaze powder comprising the following raw materials in parts by weight: 8-16 parts quartz, 2-8 parts feldspar, 10-14 parts potassium feldspar, 30-46 parts sodium feldspar, 4-9 parts limestone, 4-8 parts dolomite, and 10-16 parts crystalline composite dry granule slurry; the crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 75-85 parts ultrafine dry granules and 8-12 parts acidic yttrium aluminum composite. The crystalline glaze powder prepared by this application allows for a single firing during the preparation of crystalline ceramic tiles, ensuring the surface strength of the product, reducing overall production costs, and exhibiting good wear resistance and static friction coefficient after a single firing, with high surface smoothness. By spraying a protective glaze onto the tile surface, the crystalline glaze layer is prevented from being directly dry-polished by the grinding block during the polishing process of the semi-finished product; and color loss of the inkjet print is prevented during high-temperature firing in the kiln.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic tile technology, specifically to a crystalline glaze powder, a crystalline glaze, crystalline ceramic tiles, and a preparation method thereof. Background Technology

[0002] Currently, imitation marble tiles in the ceramic industry lack sufficient surface strength compared to natural stone, resulting in a significant difference in overall tile appearance. Imitation marble tiles utilize a conventional dry-granule stacking process, applying various effects through spraying. Multiple firings are used to increase surface strength, leading to substantial material waste. The thicker the fired surface, the higher the overall production cost. Because dry granules naturally have a low surface temperature, the high temperatures from multiple firings can affect the deformation of the entire tile. The high content of stacked dry granules also impacts tile deformation and surface smoothness after multiple firings. Therefore, existing technology cannot simultaneously balance surface strength and firing costs. A solution is needed, providing a crystalline glaze powder, crystalline glaze, crystalline tiles, and a preparation method to address these issues. Summary of the Invention

[0003] In order to overcome the shortcomings of the prior art, the present invention provides a crystalline glaze powder, a crystalline glaze, a crystalline ceramic tile, and a preparation method. The crystalline glaze powder prepared by the present application preserves the surface strength of the product itself after the ceramic tile is fired once, and avoids the waste caused by multiple firings in pursuit of process integrity.

[0004] The technical solution adopted by this invention to solve its technical problem is:

[0005] The primary objective of this application is to provide a crystalline glaze powder comprising the following raw materials in parts by weight: 8-16 parts quartz, 2-8 parts feldspar, 10-14 parts potassium feldspar, 30-46 parts sodium feldspar, 4-9 parts limestone, 4-8 parts dolomite, and 10-16 parts crystalline composite dry granule slurry.

[0006] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 75-85 parts of ultrafine dry granules and 8-12 parts of acidic yttrium aluminum composite.

[0007] The preparation method of the acidic yttrium aluminum complex includes the following process steps: mixing and stirring dilute hydrochloric acid and yttrium salt solution, adjusting pH=2, adding ammonium oxalate solution and sodium aluminate solution until precipitation is complete, heating and aging in a water bath, filtering, drying at 110℃, calcining until dry, grinding and sieving to obtain the acidic yttrium aluminum complex.

[0008] Preferably, the ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 8-10 parts high-alumina clay, 11 parts quartz, 13-18 parts black soil, 2 parts dolomite, 8-12 parts zinc oxide, and 1 part barium carbonate.

[0009] Preferably, the preparation method of the ultrafine dry granules includes the following process steps:

[0010] Prepare the raw materials according to their weight composition for ultrafine dry granules; grind each raw material into small particles to obtain a mixture; calcine and melt the mixture at 1300-1380℃ to obtain a dry granule solution; quench the dry granule solution with water and process it to 120-180 mesh to obtain ultrafine dry granules.

[0011] Preferably, the crystalline composite dry granular slurry comprises the following chemical components by mass fraction: SiO2: 18.2-24.8%; Al2O3: 8.4-12.9%; Fe2O3: 0.1-0.2%; CaO: 0.02-0.05%; MgO: 0.01%; K2O: 0.01%; Na2O: 0.01%; TiO2: 0.05-0.08%; MnO: <0.01%; P2O5: 0.03-0.05%; SO3: 0.02-0.06%; BaO: <0.01%; ZnO: <0.01%; ZrO2: 50.2-61.57%; SrO: 0.01-0.03%; and a loss on ignition of 0.1-0.2%.

[0012] Preferably, the chemical composition includes the following mass fractions: SiO2: 42.6-48.5%; Al2O3: 24.3-28.0%; Fe2O3: 0.1-0.2%; CaO: 6.5-7.8%; MgO: 2.5-3.2%; K2O: 3.4-4.2%; Na2O: 1.2-2.0%; TiO2: 0.05-0.08%; MnO: <0.01%; P2O5: 0.03-0.05%; SO3: 0.02-0.06%; BaO: 5.0-6.0%; ZnO: 1.5-2.3%; ZrO2: 0.1-0.3%; SrO: 0.01-0.03%; Y2O3: 0.03-0.06%; loss on ignition 7.0-9.5%.

[0013] Preferably, the method for preparing the crystalline composite dry granule slurry includes the following steps:

[0014] The ultrafine dry particles and the acidic yttrium aluminum composite were mixed according to a weight percentage to obtain a mixture, which was then placed in a ball mill jar. Water and methyl were added for ball milling. The feeding ratio of the mixture, water and methyl was 4:1:1 by mass, to obtain a crystalline composite dry particle slurry.

[0015] Preferably, the method for preparing the crystalline glaze powder includes the following steps:

[0016] S1. Preparation of ultrafine dry granules: Prepare materials according to the weight composition of the raw materials for ultrafine dry granules; grind each raw material into small particles to obtain a mixture; calcine the mixture at 1300-1380℃ to melt it into a dry granule solution; quench the dry granule solution with water and process it into 120-180 mesh to obtain ultrafine dry granules.

[0017] S2. Preparation of acidic yttrium aluminum complex: Mix dilute hydrochloric acid and yttrium salt solution and stir to adjust pH=2. Then add ammonium oxalate solution and sodium aluminate solution until precipitation is complete. Heat in water bath to mature, filter, dry at 110℃, calcine to dry, grind and sieve to obtain acidic yttrium aluminum complex.

[0018] S3. Preparation of crystalline composite dry granule slurry: The ultrafine dry granules and acidic yttrium aluminum composite are mixed according to the weight percentage to obtain a mixture, which is then placed in a ball mill jar, and water and methyl are added for ball milling to obtain crystalline composite dry granule slurry;

[0019] S4. Preparation of crystalline glaze powder: According to the weight composition of the raw materials of crystalline glaze powder, the solid minerals are mixed and ground evenly, and then the crystalline composite dry granule slurry is added. The mixture is calcined in a crucible at 1250-1300℃, melted for 10-15 minutes, quenched with water, crushed, ground and sieved to obtain crystalline glaze powder.

[0020] The second objective of this application is to provide a crystalline glaze, comprising the above-described crystalline glaze powder or crystalline glaze powder prepared by the above-described preparation method;

[0021] The preparation method of the crystalline glaze includes the following steps: placing the crystalline glaze powder, water, printing paste, and printing oil into a ball mill jar for ball milling for 6-8 hours, and the specific gravity of the glaze is 1.58-1.63.

[0022] The third objective of this application is to provide a crystalline ceramic tile, wherein the raw materials of the crystalline ceramic tile include the aforementioned crystalline glaze.

[0023] Preferably, the method for preparing the crystalline ceramic tile includes the following steps:

[0024] S1. Preparation of ultrafine dry granules: Prepare materials according to the weight composition of the raw materials for ultrafine dry granules; grind each raw material into small particles to obtain a mixture; calcine the mixture at 1300-1380℃ to melt it into a dry granule solution; quench the dry granule solution with water and process it into 120-180 mesh to obtain ultrafine dry granules.

[0025] S2. Preparation of acidic yttrium aluminum complex: Mix dilute hydrochloric acid and yttrium salt solution and stir to adjust pH=2. Then add ammonium oxalate solution and sodium aluminate solution until precipitation is complete. Heat in water bath to mature, filter, dry at 110℃, calcine to dry, grind and sieve to obtain acidic yttrium aluminum complex.

[0026] S3. Preparation of crystalline composite dry granule slurry: The ultrafine dry granules and acidic yttrium aluminum composite are mixed according to the weight percentage to obtain a mixture, which is then placed in a ball mill jar, and water and methyl are added for ball milling to obtain crystalline composite dry granule slurry;

[0027] S4. Preparation of crystalline glaze powder: According to the weight composition of the raw materials of crystalline glaze powder, the solid minerals are mixed and ground evenly, and then the crystalline composite dry granule slurry is added. The mixture is calcined in a crucible at 1250-1300℃, melted for 10-15 minutes, quenched with water, crushed, ground and sieved to obtain crystalline glaze powder.

[0028] S5. Preparation of crystalline glaze: Place the crystalline glaze powder, water, printing paste, and printing oil into a ball mill jar and ball mill for 6-8 hours. The specific gravity of the glaze is 1.58-1.63.

[0029] S6. Preparation of Crystalline Tiles: After the body is pressed and formed, the pattern is printed by inkjet printing. The crystalline glaze is printed on the surface of the body through a 180-mesh screen, with a sieve residue of 30-35g. A protective glaze is sprayed on by glazing. The body is fired at 1200-1230℃ for 76-82 minutes to obtain a semi-finished tile. The tile is then polished and finally baked at 250-280℃ for 3-5 minutes to obtain the crystalline tile.

[0030] The beneficial effects of this invention are:

[0031] 1. The crystalline glaze powder described in this application allows for firing only once during the preparation of crystalline ceramic tiles, ensuring the surface strength of the product and reducing the overall production cost.

[0032] 2. The crystalline ceramic tiles described in this application are fired only once, and after firing once, they have good wear resistance and static friction coefficient. The wear resistance reaches 2100 (level 4), the static friction coefficient reaches 0.76 or above, and the surface flatness reaches -0.1~+0.1, -0.15~+0.15 or -0.2~+0.2, with high surface flatness.

[0033] 3. This application prevents the semi-finished product from being directly dry-polished into a crystalline glaze layer by spraying a protective glaze onto the brick surface, thus preventing color loss of the inkjet print during high-temperature firing in the kiln. Attached Figure Description

[0034] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0035] Figure 1 This is a surface effect diagram of the crystalline ceramic tile prepared according to Example 1 of the present invention;

[0036] Figure 2 This is a magnified view of the crystalline ceramic tile prepared in Example 1 of the present invention;

[0037] Figure 3 This is a magnified view of the crystalline ceramic tile prepared in Example 7 of the present invention;

[0038] Figure 4 This is a magnified view of the crystalline ceramic tile prepared in Example 8 of the present invention;

[0039] Figure 5 This is a magnified view of the crystalline ceramic tile prepared in Example 9 of the present invention;

[0040] Figure 6 This is a magnified view of the crystalline ceramic tile prepared in Comparative Example 5 of the present invention.

[0041] Figure 7 This is a magnified view of the crystalline ceramic tile prepared in Comparative Example 6 of this invention. Detailed Implementation

[0042] The following will clearly and completely describe the concept, specific structure, and technical effects of the present invention in conjunction with embodiments and accompanying drawings, so as to fully understand the purpose, features, and effects of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention. Furthermore, all connections / linkages involved in the patent do not simply refer to direct contact between components, but rather to the ability to form a better connection structure by adding or reducing connecting accessories according to specific implementation conditions. The various technical features in this invention can be combined interactively without contradicting each other.

[0043] All raw materials or reagents used in the embodiments and comparative examples of this invention were purchased from mainstream manufacturers on the market. Those without specified manufacturers or concentrations are all analytical grade raw materials or reagents that are routinely available. There are no particular restrictions as long as they achieve the expected effect. The microscopes and other instruments used in this embodiment were all purchased from major manufacturers on the market. There are no particular limitations as long as they achieve the expected effect. Where specific techniques or conditions are not specified in this embodiment, they should be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions.

[0044] In the embodiments and comparative examples of this application, the raw materials for the crystalline composite dry granule slurry were formulated, and the chemical composition, by weight percentage, met the following requirements: SiO2: 18.2-24.8%; Al2O3: 8.4-12.9%; Fe2O3: 0.1-0.2%; CaO: 0.02-0.05%; MgO: 0.01%; K2O: 0.01%; Na2O: 0.01%; TiO2: 0.05-0.08%; MnO: <0.01%; P2O5: 0.03-0.05%; SO3: 0.02-0.06%; BaO: <0.01%; ZnO: <0.01%; ZrO2: 50.2-61.57%; SrO: 0.01-0.03%; Loss on ignition 0.1-0.2%.

[0045] In the embodiments and comparative examples of this application, the raw materials of the crystalline glaze powder were formulated, and the chemical composition, by weight percentage, met the following requirements: SiO2: 42.6-48.5%; Al2O3: 24.3-28.0%; Fe2O3: 0.1-0.2%; CaO: 6.5-7.8%; MgO: 2.5-3.2%; K2O: 3.4-4.2%; Na2O: 1.2-2.0%; TiO2: 0.05-0.08%; MnO: <0.01%; P2O5: 0.03-0.05%; SO3: 0.02-0.06%; BaO: 5.0-6.0%; ZnO: 1.5-2.3%; ZrO2: 0.1-0.3%; SrO: 0.01-0.03%; Y2O3: 0.03-0.06%; Loss on ignition 7.0-9.5%.

[0046] Example 1

[0047] A crystalline glaze powder comprises the following raw materials in parts by weight: 8 parts quartz, 4 parts feldspar, 12 parts potassium feldspar, 38 parts sodium feldspar, 7 parts limestone, 6 parts dolomite, and 10 parts crystalline composite dry granule slurry.

[0048] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 78 parts ultrafine dry granules and 8 parts acidic yttrium aluminum composite;

[0049] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 8 parts high-alumina clay, 11 parts quartz, 13 parts black soil, 2 parts dolomite, 8 parts zinc oxide, and 1 part barium carbonate.

[0050] The method for preparing the above-mentioned crystalline powder includes the following steps:

[0051] S1. Preparation of ultrafine dry granules: Prepare materials according to the weight composition of the raw materials for ultrafine dry granules; grind each raw material into small particles to obtain a mixture; calcine the mixture at 1300-1380℃ to melt it into a dry granule solution; quench the dry granule solution with water and process it to 120-180 mesh to obtain ultrafine dry granules.

[0052] S2. Preparation of acidic yttrium aluminum composite: Prepare raw materials according to the chemical composition of the acidic yttrium aluminum composite. Adjust the pH of the yttrium salt solution to 2 with dilute hydrochloric acid. During stirring, add ammonium oxalate solution and sodium aluminate solution simultaneously, with the ratio of ammonium oxalate solution to sodium aluminate solution being 2:1. Stop adding the solution when precipitation is complete. Then heat and mature in an 80°C water bath for 30 minutes. Filter, dry at 110°C, and calcine at 900-1000°C until dry. Grind and sieve to form an 80-100 mesh acidic yttrium aluminum composite.

[0053] The preparation of yttrium salt solution, the main component of which is yttrium chloride; ammonium oxalate solution is a commonly used industrial solution; sodium aluminate solution is sodium aluminate powder dissolved in water, wherein the mass ratio of sodium aluminate powder to water is 1:3.

[0054] S3. Preparation of crystalline composite dry granule slurry: Prepare raw materials according to the chemical composition of crystalline composite dry granule slurry; mix ultrafine dry granules and acidic yttrium aluminum composite according to weight percentage to obtain a mixture, put it into a ball mill jar, add water and methyl to ball mill and obtain crystalline composite dry granule slurry; wherein, the feeding ratio of the mixture, water and methyl is, according to the mass ratio, mixture:water:methyl = 4:1:1, where methyl is sodium carboxymethyl cellulose commonly used in glazes.

[0055] The ball milling process involves using 600g of high-alumina ball milling balls, including 80g of ball milling balls with a diameter of 2.5-4mm, 200g of ball milling balls with a diameter of 3-6mm, and 220g of ball milling balls with a diameter of 6-10mm. The mixture is then ball milled for 40 minutes.

[0056] S4. Preparation of crystalline glaze powder: According to the weight composition of the raw materials for crystalline glaze powder, the solid minerals are mixed and ground evenly. The corresponding crystalline composite dry granule slurry is slowly added to the mixed materials. The mixture is placed in a crucible calcined to 1250-1300℃ in a high-temperature furnace, melted for 10-15 minutes, quenched with water, crushed and ground to make glaze powder, and sieved through 100 mesh to obtain crystalline glaze powder.

[0057] A method for preparing a crystalline glaze includes the following steps:

[0058] S5. Preparation of crystalline glaze: The crystalline glaze powder obtained in step S4 above is added to water, printing paste, and printing oil and placed in a ball mill jar for ball milling. The ball milling time is 6-8 hours, and the specific gravity of the glaze is 1.58-1.63 to obtain crystalline glaze.

[0059] The ball milling process involves using 600g of high-alumina ball milling balls, including 80g of ball milling balls with a diameter of 2.5-4mm, 200g of ball milling balls with a diameter of 3-6mm, and 220g of ball milling balls with a diameter of 6-10mm, and mixing them for ball milling.

[0060] A method for preparing crystalline ceramic tiles includes the following steps:

[0061] S6. Preparation of Crystalline Tiles: After the body is pressed and formed, an inkjet printed pattern is applied. The crystalline glaze prepared in step S5 is then screen-printed onto the surface of the body using a 180-mesh screen, with a residue of 30-35g. A layer of conventional tile protective glaze is then sprayed on using a splatter method, with a spray specific gravity of (1.32-1.36). The glazed body is then fired at 1200-1230℃ for 76-82 minutes to obtain a semi-finished tile. This semi-finished tile is then polished and finally baked at 250-280℃ for 3-5 minutes to obtain the crystalline tile. Figure 1-2 As shown.

[0062] Example 2

[0063] A crystalline glaze powder comprises the following raw materials in parts by weight: 16 parts quartz, 8 parts feldspar, 14 parts potassium feldspar, 46 parts sodium feldspar, 9 parts limestone, 8 parts dolomite, and 16 parts crystalline composite dry granule slurry.

[0064] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 85 parts ultrafine dry granules and 12 parts acidic yttrium aluminum composite.

[0065] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 8 parts high-alumina clay, 11 parts quartz, 14 parts black soil, 2 parts dolomite, 8 parts zinc oxide, and 1 part barium carbonate.

[0066] The preparation method is the same as in Example 1.

[0067] Example 3

[0068] A crystalline glaze powder comprises the following raw materials in parts by weight: 8 parts quartz, 2 parts feldspar, 10 parts potassium feldspar, 30 parts sodium feldspar, 4 parts limestone, 4 parts dolomite, and 10 parts crystalline composite dry granule slurry.

[0069] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 75 parts ultrafine dry granules and 8 parts acidic yttrium aluminum composite.

[0070] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 9 parts high-alumina clay, 11 parts quartz, 15 parts black soil, 2 parts dolomite, 9 parts zinc oxide, and 1 part barium carbonate.

[0071] The preparation method is the same as in Example 1.

[0072] Example 4

[0073] A crystalline glaze powder comprises the following raw materials in parts by weight: 12 parts quartz, 6 parts feldspar, 11 parts potassium feldspar, 40 parts sodium feldspar, 6 parts limestone, 6 parts dolomite, and 13 parts crystalline composite dry granule slurry.

[0074] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 80 parts ultrafine dry granules and 10 parts acidic yttrium aluminum composite.

[0075] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 9 parts high-alumina clay, 11 parts quartz, 16 parts black soil, 2 parts dolomite, 10 parts zinc oxide, and 1 part barium carbonate.

[0076] The preparation method is the same as in Example 1.

[0077] Example 5

[0078] A crystalline glaze powder comprises the following raw materials in parts by weight: 10 parts quartz, 4 parts feldspar, 12 parts potassium feldspar, 42 parts sodium feldspar, 7 parts limestone, 5 parts dolomite, and 16 parts crystalline composite dry granule slurry.

[0079] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 82 parts of ultrafine dry granules and 11 parts of acidic yttrium aluminum composite;

[0080] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 10 parts high-alumina clay, 11 parts quartz, 17 parts black soil, 2 parts dolomite, 11 parts zinc oxide, and 1 part barium carbonate.

[0081] The preparation method is the same as in Example 1.

[0082] Example 6

[0083] A crystalline glaze powder comprises the following raw materials in parts by weight: 14 parts quartz, 6 parts feldspar, 13 parts potassium feldspar, 35 parts sodium feldspar, 5 parts limestone, 7 parts dolomite, and 12 parts crystalline composite dry granule slurry.

[0084] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 84 parts ultrafine dry granules and 9 parts acidic yttrium aluminum composite;

[0085] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 10 parts high-alumina clay, 11 parts quartz, 18 parts black soil, 2 parts dolomite, 12 parts zinc oxide, and 1 part barium carbonate.

[0086] The preparation method is the same as in Example 1.

[0087] Comparative Example 1

[0088] A crystalline glaze powder comprises the following raw materials in parts by weight: 8 parts quartz, 4 parts feldspar, 12 parts potassium feldspar, 38 parts sodium feldspar, 7 parts limestone, and 6 parts dolomite.

[0089] The method for preparing the above-mentioned crystalline powder includes the following steps:

[0090] S4. Preparation of crystalline glaze powder: According to the weight composition of the raw materials for crystalline glaze powder, the solid minerals are mixed and ground evenly, placed in a crucible calcined to 1250-1300℃ in a high-temperature furnace, melted for 10-15 minutes, quenched with water, crushed and ground to make glaze powder, and sieved through 100 mesh to obtain crystalline glaze powder.

[0091] A method for preparing a crystalline glaze includes the following steps:

[0092] S5. Preparation of crystalline glaze: The crystalline glaze powder obtained in step S4 above is added to water, printing paste, and printing oil and placed in a ball mill jar for ball milling. The ball milling time is 6-8 hours, and the specific gravity of the glaze is 1.58-1.63 to obtain crystalline glaze.

[0093] A method for preparing crystalline ceramic tiles includes the following steps:

[0094] S6. Preparation of Crystalline Tiles: After the body is pressed and formed, an inkjet printed pattern is applied. The crystalline glaze prepared in step S5 is then screen-printed onto the surface of the body using a 180-mesh screen, with a residue of 30-35g. A layer of conventional tile protective glaze is then sprayed on using a splatter method, with a spray specific gravity of (1.32-1.36). The glazed body is then fired at a temperature of 1200-1230℃ for 76-82 minutes to obtain a semi-finished tile. This semi-finished tile is then polished and finally baked at 250-280℃ for 3-5 minutes to obtain the crystalline tile.

[0095] Comparative Example 2

[0096] A crystalline glaze powder comprises the following raw materials in parts by weight: 16 parts quartz, 8 parts feldspar, 14 parts potassium feldspar, 46 parts sodium feldspar, 9 parts limestone, 8 parts dolomite, and 16 parts crystalline composite dry granule slurry.

[0097] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 85 parts of ultrafine dry granules;

[0098] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 8 parts high-alumina clay, 11 parts quartz, 14 parts black soil, 2 parts dolomite, 8 parts zinc oxide, and 1 part barium carbonate.

[0099] The method for preparing the above-mentioned crystalline powder includes the following steps:

[0100] S1. Preparation of ultrafine dry granules: Prepare materials according to the weight composition of the raw materials for ultrafine dry granules; grind each raw material into small particles to obtain a mixture; calcine the mixture at 1300-1380℃ to melt it into a dry granule solution; quench the dry granule solution with water and process it to 120-180 mesh to obtain ultrafine dry granules.

[0101] S3. Preparation of crystalline composite dry granule slurry: Prepare raw materials according to the chemical composition of crystalline composite dry granule slurry; put ultrafine dry granules into a ball mill jar, add water and methyl groups for ball milling, wherein the feeding ratio of ultrafine dry granules, water and methyl groups is, by mass ratio, ultrafine dry granules: water: methyl groups = 4:1:1, to obtain crystalline composite dry granule slurry.

[0102] The ball milling process involves using 600g of high-alumina ball milling balls, including 80g of ball milling balls with a diameter of 2.5-4mm, 200g of ball milling balls with a diameter of 3-6mm, and 220g of ball milling balls with a diameter of 6-10mm. The mixture is then ball milled for 40 minutes.

[0103] S4. Preparation of crystalline glaze powder: According to the weight composition of the raw materials for crystalline glaze powder, the solid minerals are mixed and ground evenly. The corresponding crystalline composite dry granule slurry is slowly added to the mixed materials. The mixture is placed in a crucible calcined to 1250-1300℃ in a high-temperature furnace, melted for 10-15 minutes, quenched with water, crushed and ground to make glaze powder, and sieved through 100 mesh to obtain crystalline glaze powder.

[0104] A method for preparing a crystalline glaze includes the following steps:

[0105] S5. Preparation of crystalline glaze: The crystalline glaze powder obtained in step S4 above is added to water, printing paste, and printing oil and placed in a ball mill jar for ball milling. The ball milling time is 6-8 hours, and the specific gravity of the glaze is 1.58-1.63 to obtain crystalline glaze.

[0106] A method for preparing crystalline ceramic tiles includes the following steps:

[0107] S6. Preparation of Crystalline Tiles: After the body is pressed and formed, an inkjet printed pattern is applied. The crystalline glaze prepared in step S5 is then screen-printed onto the surface of the body using a 180-mesh screen, with a residue of 30-35g. A layer of conventional tile protective glaze is then sprayed on using a splatter method, with a spray specific gravity of (1.32-1.36). The glazed body is then fired at a temperature of 1200-1230℃ for 76-82 minutes to obtain a semi-finished tile. This semi-finished tile is then polished and finally baked at 250-280℃ for 3-5 minutes to obtain the crystalline tile.

[0108] Comparative Example 3

[0109] A crystalline glaze powder comprises the following raw materials in parts by weight: 10 parts quartz, 4 parts feldspar, 12 parts potassium feldspar, 42 parts sodium feldspar, 7 parts limestone, 5 parts dolomite, and 16 parts crystalline composite dry granule slurry.

[0110] The crystalline composite dry granule slurry comprises the following raw materials in parts by weight: 82 parts of ultrafine dry granules and 18 parts of acidic yttrium aluminum composite.

[0111] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 10 parts high-alumina clay, 11 parts quartz, 17 parts black soil, 2 parts dolomite, 11 parts zinc oxide, and 1 part barium carbonate.

[0112] The preparation method is the same as in Example 1.

[0113] Comparative Example 4

[0114] A crystalline glaze powder comprises the following raw materials in parts by weight: 8 parts quartz, 4 parts feldspar, 12 parts potassium feldspar, 38 parts sodium feldspar, 7 parts limestone, 6 parts dolomite, and 23 parts crystalline composite dry granule slurry.

[0115] Other conditions are the same as in Example 1.

[0116] The crystalline ceramic tiles prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to product performance testing.

[0117] 1. Abrasion resistance and static friction coefficient test: The crystalline ceramic tiles prepared in Examples 1-6 and Comparative Examples 1-4 were tested using the test method of GB / T3810.7-2016. The degree of surface wear marks after grinding at a specific number of grinding revolutions was observed and divided into 0-5 levels. The test results are shown in Table 1 below:

[0118] Table 1

[0119]

[0120] 2. Brick Surface Flatness Test: The ceramic tiles prepared in Examples 1-6 and Comparative Examples 1-4 were tested for flatness using a deformable ruler placed on the tile surface and a feeler gauge. The test results are shown in Table 2 below:

[0121] Table 2

[0122]

[0123] As can be seen from Table 2 above, the crystalline ceramic tiles prepared in Examples 1-6 of this application all have a wear resistance of 2100 (level 4), a static friction coefficient of 0.76 or higher, and a surface flatness of -0.1~+0.1, -0.15~+0.15 or -0.2~+0.2, indicating high surface flatness.

[0124] Comparative Example 1: Crystallized glaze powder without the addition of crystalline composite dry granule slurry. The resulting crystalline ceramic tile has an abrasion resistance of only 750 (second level), a static friction coefficient of 0.62-0.64, and a surface flatness of -0.4 to +0.4. The abrasion resistance and static friction coefficient are significantly reduced, and the surface flatness is worse than that of Examples 1-6.

[0125] Comparative Example 2: In the crystalline composite dry granule slurry used to prepare crystalline glaze powder, no acidic yttrium aluminum composite was added. The resulting crystalline ceramic tile had an abrasion resistance of 1500 (level 3), a static friction coefficient of 0.64-0.66, and a surface flatness of -0.5 to +0.5. The abrasion resistance and static friction coefficient were significantly reduced, and the surface flatness was significantly worse than in Examples 1-6.

[0126] In Comparative Example 3, an excessive amount of acidic yttrium aluminum composite was added during the preparation of the crystalline composite dry granule slurry. The resulting crystalline ceramic tile had an abrasion resistance of 2100 (level 4) and a static friction coefficient of 0.8-0.82. However, the surface flatness of the tile was -0.75 to +0.75. Although the abrasion resistance and static friction coefficient met higher requirements, the surface flatness of the tile was significantly worse, and the deformation of the tile could not be controlled during the firing process.

[0127] In Comparative Example 4, an excessive amount of crystalline composite dry granule slurry was added during the preparation of crystalline glaze powder. The resulting crystalline ceramic tile had an abrasion resistance of 2100 (level 4) and a static friction coefficient of 0.8-0.82. However, the surface flatness of the tile was -0.7 to +0.7. Although the abrasion resistance and static friction coefficient met higher requirements, the surface flatness of the tile was significantly worse, and the deformation of the tile could not be controlled during the firing process.

[0128] As can be seen from the above data, when preparing crystalline ceramic tiles, adding the crystalline composite dry granule paste prepared in this application to the original mineral composition significantly improves the wear resistance and static friction coefficient, and also provides better tile surface flatness.

[0129] Example 7

[0130] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 8 parts high-alumina clay, 11 parts quartz, 18 parts black soil, 2 parts dolomite, 8 parts zinc oxide, and 1 part barium carbonate; other conditions are the same as in Example 1.

[0131] Example 8

[0132] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 9 parts high-alumina clay, 11 parts quartz, 16 parts black soil, 2 parts dolomite, 10 parts zinc oxide, and 1 part barium carbonate; other conditions are the same as in Example 1.

[0133] Example 9

[0134] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 10 parts high-alumina clay, 11 parts quartz, 13 parts black soil, 2 parts dolomite, 12 parts zinc oxide, and 1 part barium carbonate; other conditions are the same as in Example 1.

[0135] Comparative Example 5

[0136] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 5 parts high-alumina clay, 11 parts quartz, 10 parts black soil, 2 parts dolomite, 5 parts zinc oxide, and 1 part barium carbonate; other conditions are the same as in Example 1.

[0137] Comparative Example 6

[0138] The ultrafine dry particles comprise the following raw materials in parts by weight: 48 parts potassium feldspar, 12 parts high-alumina clay, 11 parts quartz, 22 parts black soil, 2 parts dolomite, 15 parts zinc oxide, and 1 part barium carbonate; other conditions are the same as in Example 1.

[0139] The crystalline ceramic tiles prepared in Examples 7-9 and Comparative Examples 5-6 were subjected to product performance testing.

[0140] Surface pore condition testing: The crystalline ceramic tiles prepared in Examples 7-9 and Comparative Examples 5-6 were placed under a microscope, and the condition of the tiles after exiting the kiln was observed. The results are shown in Table 3 below: Table 3

[0141]

[0142] As can be seen from Table 3 above, such as Figure 3-5As shown, the crystalline ceramic tiles prepared in Examples 7-9 of this application have smaller and finer pores on the tile surface, and the multiple glazes are well bonded, which can effectively solve the problem of dirt absorption on the tile surface. Comparative Example 5, due to insufficient use of ultrafine dry granule raw materials, has larger pores on the tile surface, posing a greater risk of dirt absorption. Figure 6 As shown in the figure; however, in Comparative Example 6, due to excessive use of ultrafine dry granule raw materials, the fluidity of the crystalline glaze slurry decreased after pelletizing. Even after being left to stand for two or three days after pelletizing, there were still many bubbles, and the glaze slurry had a "tofu-like" state. After glazing, it resulted in pinholes or pits, causing thixotropy of the glaze surface and rendering it unusable. Figure 7 As shown.

[0143] The above is a detailed description of the preferred embodiments of the present invention. However, the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention. All such equivalent modifications or substitutions are included within the scope defined by the claims of this application.

Claims

1. A crystalline glaze powder, characterized by, The raw materials include the following components by weight: quartz stone 8-16 parts, Changbai stone 2-8 parts, potassium feldspar 10-14 parts, sodium feldspar 30-46 parts, limestone 4-9 parts, dolomite 4-8 parts, and crystalline composite dry granular slurry 10-16 parts; The crystalline composite dry granular slurry includes the following components by weight: superfine dry granules 75-85 parts, and acidic yttrium-aluminum composite 8-12 parts; The preparation method of the acidic yttrium-aluminum composite includes the following steps: mixing dilute hydrochloric acid and yttrium salt solution, adjusting PH to 2, adding ammonium oxalate solution and sodium metaaluminate solution until the precipitation is complete, water bath heating and aging, filtering, drying at 110℃, calcining to dryness, and grinding and sieving to obtain the acidic yttrium-aluminum composite; The superfine dry granules include the following components by weight: potassium feldspar 48 parts, high-alumina soil block 8-10 parts, quartz stone 11 parts, black soil 13-18 parts, dolomite 2 parts, zinc oxide 8-12 parts, and barium carbonate 1 part.

2. A crystalline glaze powder according to claim 1, wherein The preparation method of the superfine dry granules includes the following steps: According to the weight composition of the raw materials of the superfine dry granules, the materials are prepared; each raw material is ground to a small particle state to obtain a mixture; the mixture is calcined and melted at 1300-1380℃ to obtain a dry granule melt, and the dry granule melt is water quenched and processed into 120-180 mesh to obtain the superfine dry granules.

3. A crystalline glaze powder according to claim 1, wherein The raw materials of the crystalline flower glaze powder include the following chemical components by mass fraction: SiO2: 42.6-48.5%; Al2O3: 24.3-28.0%; Fe2O3: 0.1-0.2%; CaO: 6.5-7.8%; MgO: 2.5-3.2%; K2O: 3.4-4.2%; Na2O: 1.2-2.0%; TiO2: 0.05-0.08%; MnO: <0.01%; P2O5: 0.03-0.05%; SO3: 0.02-0.06%; BaO: 5.0-6.0%; ZnO: 1.5-2.3%; ZrO2: 0.1-0.3%; SrO: 0.01-0.03%; Y2O3: 0.03-0.06%; and loss on ignition: 7.0-9.5%.

4. The crystalline glaze powder of claim 1, wherein, The preparation method of the crystalline composite dry granular slurry includes the following steps: The superfine dry granules and the acidic yttrium-aluminum composite are mixed according to the weight percentage to obtain a mixture, which is put into a ball mill tank, water and sodium carboxymethyl cellulose are added for ball milling treatment, wherein the feeding ratio of the mixture, water and sodium carboxymethyl cellulose is mixture: water: sodium carboxymethyl cellulose = 4: 1: 1 by mass ratio, to obtain the crystalline composite dry granular slurry.

5. A crystalline glaze powder according to any one of claims 1 to 4, characterized in that The preparation method of the crystalline flower glaze powder includes the following steps: S1, preparation of superfine dry granules: according to the weight composition of the raw materials of the superfine dry granules, the materials are prepared; each raw material is ground to a small particle state to obtain a mixture; the mixture is calcined and melted at 1300-1380℃ to obtain a dry granule melt, and the dry granule melt is water quenched and processed into 120-180 mesh to obtain the superfine dry granules; S2, preparation of acidic yttrium aluminum complex: dilute hydrochloric acid and yttrium salt solution is mixed and stirred, adjust PH = 2, then add ammonium oxalate solution and sodium metaaluminate solution, until the precipitation is complete, water bath heating, filtration, drying at 110 DEG C, calcination to dryness, grinding sieve to get acidic yttrium aluminum complex; S3, preparation of crystalline composite dry particle slurry: the superfine dry particle and the acidic yttrium aluminum complex are mixed according to the weight percentage to obtain a mixture, which is put into a ball mill tank, water and sodium carboxymethyl cellulose are added for ball milling treatment to obtain the crystalline composite dry particle slurry; S4, preparation of crystalline flower glaze powder: according to the weight composition of the raw materials of the crystalline flower glaze powder, the solid minerals are mixed and ground uniformly, then the crystalline composite dry particle slurry is added, calcination is carried out in a crucible at 1250-1300 DEG C, water quenching is carried out after melting for 10-15 min, crushing and grinding are carried out, and sieving is carried out to obtain the crystalline flower glaze powder.

6. A crystalline glaze, characterized by, The crystalline flower glaze powder prepared by the preparation method of claim 5 is also included. The preparation method of the crystalline flower glaze comprises the following steps: the crystalline flower glaze powder, water, printing paste and printing oil are put into a ball mill tank for ball milling treatment, the ball milling time is 6-8 h, and the glaze specific gravity is 1.58-1.

63.

7. A crystallized ceramic tile, characterized by, The raw materials of the crystalline ceramic tile include the crystalline flower glaze of claim 6.

8. The method of claim 7, wherein the crystalline ceramic tile is prepared by the steps of: The preparation method comprises the following steps: S1, preparation of superfine dry particle: according to the weight composition of the raw materials of the superfine dry particle, the raw materials are prepared; the raw materials are ground into small particle state to obtain a mixture; the mixture is calcined and melted at 1300-1380 DEG C to obtain dry particle melt, the dry particle melt is water quenched to obtain 120-180 mesh superfine dry particle; S2, preparation of acidic yttrium aluminum complex: dilute hydrochloric acid and yttrium salt solution is mixed and stirred, adjust PH = 2, then add ammonium oxalate solution and sodium metaaluminate solution, until the precipitation is complete, water bath heating, filtration, drying at 110 DEG C, calcination to dryness, grinding sieve to get acidic yttrium aluminum complex; S3, preparation of crystalline composite dry particle slurry: the superfine dry particle and the acidic yttrium aluminum complex are mixed according to the weight percentage to obtain a mixture, which is put into a ball mill tank, water and sodium carboxymethyl cellulose are added for ball milling treatment to obtain the crystalline composite dry particle slurry; S4, preparation of crystalline flower glaze powder: according to the weight composition of the raw materials of the crystalline flower glaze powder, the solid minerals are mixed and ground uniformly, then the crystalline composite dry particle slurry is added, calcination is carried out in a crucible at 1250-1300 DEG C, water quenching is carried out after melting for 10-15 min, crushing and grinding are carried out, and sieving is carried out to obtain the crystalline flower glaze powder; S5, preparation of crystalline flower glaze: the crystalline flower glaze powder, water, printing paste and printing oil are put into a ball mill tank for ball milling treatment, the ball milling time is 6-8 h, and the glaze specific gravity is 1.58-1.

63. S6, preparation of the crystalline ceramic tile: after the body is press-formed, the pattern is inkjet printed, the crystalline glaze is printed on the body surface through a 180-mesh screen, the amount of residue is 30-35 g, and the protective glaze is sprayed in the form of glaze throwing, and the ceramic tile semi-finished product is obtained by firing at a temperature of 1200-1230 DEG C for 76-82 min, polished, and finally baked at a temperature of 250-280 DEG C for 3-5 min to obtain the crystalline ceramic tile.

Citation Information

Patent Citations

  • Crystal flower dry granular glaze and locating crystal flower ceramic tile prepared through crystal flower dry granular glaze

    CN110759641A

  • Marble crystal glaze, marble tile using same and preparation process

    CN116143410A